Cross-Sectional Survey of the Training Practices of Racing Greyhounds in New Zealand - Palmer, Anna L. (Animals (Basel), 2020)
SIMPLE SUMMARY: There is a limited amount of scientific literature about the training of racing greyhounds. Previous reports have focused on racing injuries, race-track designs, and genetic traits of racing greyhounds, with little attention to training practices. Training and racing workload have been suggested as important factors associated with racing greyhound welfare and success. In this study, training practices of racing greyhounds were described by New Zealand trainers using a pro forma survey. We found that trainers considered similar factors, (1) the ability to reach time milestones and (2) the appearance of young dogs, which indicated when they were ready to begin formal race training and racing, to be important when training young greyhounds. Training programmes for race-fit greyhounds were structured around a weekly cycle of two gallop workouts or races a few days apart, separated by walking and free exercise. Training practices appear to be specific to the metabolic and physiologic adaptations required for the challenges associated with sprint racing. This description of training practices provides baseline information about the workload of racing greyhounds in New Zealand. ABSTRACT: The aim of this study was to conduct a cross-sectional survey of racing greyhound trainers in New Zealand in order to provide an overview of their training practices. A survey regarding training practices was posted to all registered greyhound training license holders in New Zealand in August 2019. Data were collected from a convenience sample of 48 trainers (35.6%; n = 48/137) who completed the survey. Other than the differences in the number of greyhounds in race training, the training programmes described by public trainers and owner trainers were similar. Trainers reported that the primary reason for registering young dogs for racing and for qualifying for racing was the ability to meet time milestones. Young dogs had a median of six (interquartile range (IQR): 4–10) trials before they commenced their racing career. Trainers described training practices that aimed to prepare greyhounds for race-day. Regardless of whether the dogs raced once or twice a week, most training programmes demonstrated high specificity where training involved two periods of load cycles through high-intensity workload. Trainers racing their greyhounds once a week simulated the workload of trainers racing their greyhounds twice a week by introducing one high-intensity (speed) workout during the week. Training programmes were structured to condition the dogs to the physiological and metabolic requirements of sprint racing. This study highlights the importance of the need for an improved understanding of training and competition load in order to enable future research in the field of racing greyhounds.